Insights of Rashtriya Bal Swasthya Karyakram: a strength, weaknesses, opportunities, and threats analysis - A. S., Hema Priya; S. R., Arun Krishna; Sundar, Jasmine S. (International Journal Of Community Medicine And Public Health, 2022)
Over 400 million children between 0 and 18 live in India, making it the world’s largest country for children. Out of every 100 newborns, 6 to 7 are estimated to have birth abnormalities and a significant fraction of children experience nutritional inadequacies and developmental impairments. Rashtriya Bal Swasthya Karyakram (RBSK), a programme created to enhance the health of children from birth to 18 years of age through early identification, prevention, and management of 30 health conditions under the 4Ds, was introduced in 2013 by the ministry of health and family welfare to mitigate these downsides. This review study aims to gain insight into the RBSK program using the strength, weaknesses, opportunities, and threats (SWOT) analysis. All articles regarding the programme had been systematically searched using published scholarly databases, PubMed, and search engines like google as well as within the grey literature. All considerations were then organized thematically into risks and potential chances to improve its effectiveness, as well as strengths and weaknesses that address the survival outcome of the RBSK scheme. As a result, the dearth of service providers, a certain lack of diagnostic resources, and technological development are the downsides, while probable threats include ignorance and abandoning treatment. To enhance the quality of life for children, it is also crucial to encourage early identification and care, which reduces the risk of delayed diagnosis. To fix the weaknesses, avoid threats, and take advantage of all future opportunities to overcome the addressed issues, RBSK needs to be upgraded.